Ultrahigh-density fine-grain ruthenium-tantalum alloy target material and preparation method thereof

Through ball milling and mixing powder, low-pressure pre-pressing, hydrogen reduction and discharge plasma sintering, ultra-high density fine grain ruthenium tantalum alloy targets are prepared, solving the density and grain size of existing RuTa targets and improving the magnetic Control sputtering performance and film quality.

CN119216579APending Publication Date: 2024-12-31YUNNAN PRECIOUS METALS LAB CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411352497.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing RuTa targets have poor density, resulting in poor magnetron sputtering performance, unstable film performance, and grains prepared by smelting at high Ru content are difficult to refine. The vacuum heat pressing method has low density and is not suitable for magnetron Sputtering.

Method used

The ultra-high-density fine grained ruthenium tantalum alloy target is prepared by using ball milling powder mixing, low-pressure prepressing, hydrogen reduction, discharge plasma sintering and low-pressure sintering, and the target density and grain refinement are improved through precision machining. Improve magnetron sputtering performance.

Benefits of technology

The density and grain refinement of the ruthenium tantalum alloy target material are significantly improved, its adaptability to magnetron sputtering is enhanced, the stability and uniformity of the film are improved, and the performance of the film for the final integrated circuit is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119216579A_ABST
    Figure CN119216579A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrahigh-density fine-grain ruthenium-tantalum alloy target material and a preparation method thereof, and belongs to the technical field of alloy target material preparation. The method comprises the following steps: (1) mixing powder; (2) low-pressure pre-pressing; (3) hydrogen reduction; (4) spark plasma sintering; (5) low-pressure sintering; and (6) precision machining. The density of the ruthenium-tantalum alloy target material prepared through the method can reach 99.8% or above, the grain size of the target material can reach 5 [mu] m or below, excellent magnetron sputtering technology adaptability is achieved, an excellent basis is provided for subsequent magnetron sputtering technology preparation of a thin film for an integrated circuit, and the method is suitable for industrial production. And the prepared thin film for the integrated circuit has relatively excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy target material preparation, and relates to an ultra-high dense fine-grained ruthenium-tantalum alloy target material and a preparation method thereof. Background Art

[0002] RuTa target is one of the commonly used diffusion barrier target materials in Cu interconnection process. Magnetron sputtering technology is usually used to prepare RuTa thin film between Si / SiO2 layer and Cu layer to prevent the mutual diffusion of Si / SiO2 and Cu. In the process of magnetron sputtering, the properties of the target material itself directly affect the efficiency of magnetron sputtering and the performance of the sputtered film. Among them, the density of the target material and the internal grain size are the key factors affecting the magnetron sputtering performance of the target material itself. The density is poor, and there are many defects such as pores inside the target material. In the process of magnetron sputtering, the defects are excited, which affects the sputtering deposition rate and the formation of thin film particles in the sputtering deposition process, resulting in poor stability of the magnetron sputtering process. Finally, the film prepared by magnetron sputtering technology has poor performance. The large grain size makes it easy to produce uneven thickness of deposits on the surface of the target material, forming accumulation blocks, which has a great negative impact on the performance of the film.

[0003] At present, the preparation methods of RuTa targets usually include smelting method, vacuum hot pressing method, etc. Among them, the alloy target materials prepared by smelting method have larger grains. In order to meet the sputtering requirements, they usually need to be combined with heat treatment, rolling and other processes. The production cycle is long, and when the Ru content is high, the plasticity of the smelted ingot is poor, and rolling is more difficult, resulting in difficulty in grain refinement. The alloy target materials prepared by vacuum hot pressing method have lower density, which is not conducive to the use of magnetron sputtering technology to prepare the final product.

[0004] Therefore, it is necessary to provide an ultra-high density fine-grained ruthenium-tantalum alloy target material and a preparation method thereof to improve the sputtering performance of the target material, improve the adaptability of the target material to magnetron sputtering technology, and thereby improve the performance of thin films used in the preparation of integrated circuits by magnetron sputtering technology. Summary of the invention

[0005] In order to overcome the problems in the background technology, the present invention optimizes the preparation method to achieve the purpose of improving the density of the ruthenium-tantalum alloy target and refining the alloy grains, thereby making the sputtering performance of the ruthenium-tantalum alloy target better, and ultimately improving the performance of the thin film for integrated circuits prepared by magnetron sputtering technology.

[0006] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0007] In one aspect, the present invention provides a method for preparing an ultra-high-density fine-grained ruthenium-tantalum alloy target, the preparation method comprising the following steps:

[0008] (1) Powder mixing: In an argon atmosphere, metal ruthenium powder and tantalum powder are placed in a ball mill, and then ball milled to mix the powders to obtain a mixed powder;

[0009] (2) low-pressure pre-pressing: the mixed powder obtained in step (1) is placed in a graphite mold and subjected to low-pressure pre-pressing to obtain a pre-pressed blank;

[0010] (3) Hydrogen reduction: placing the pre-pressed blank obtained in step (2) into a tubular reduction furnace for hydrogen reduction;

[0011] (4) Spark plasma sintering: placing the preform after hydrogen reduction in step (3) into a spark plasma sintering furnace, and performing spark plasma sintering on the preform to obtain a spark plasma sintered blank;

[0012] (5) low-pressure sintering: under argon pressure, the spark plasma sintered blank obtained in step (4) is subjected to low-pressure sintering treatment to obtain an ultra-high-density fine-grained ruthenium-tantalum alloy ingot;

[0013] (6) Precision machining: performing surface grinding on the ultra-high density fine-grained ruthenium-tantalum sintered ingot in step (5) to obtain an ultra-high density fine-grained ruthenium-tantalum alloy target.

[0014] Preferably, in step (1), a plasma ball mill is used for ball milling and powder mixing, the ball-to-material ratio is 10 to 30:1, the ball milling frequency is 8 to 10 kHz, and the ball milling mixing time is 8 to 10 hours.

[0015] Preferably, in step (1), the purity of the metal ruthenium powder and tantalum powder is ≥99.99%, the particle size of the ruthenium powder is 1 to 5 μm, and the particle size of the tantalum powder is 5 to 20 μm.

[0016] Preferably, in step (2), the pressing pressure is 10 to 20 MPa, and the holding time is 30 to 60 min.

[0017] Preferably, in step (3), the hydrogen reduction temperature is 500-700° C., the hydrogen pressure is 0.5-5 MPa, and the reduction time is 3-5 h.

[0018] In the step (4), the spark plasma sintering temperature is 1200-1350° C., the sintering time is 10-30 min, and the sintering pressure is 30-50 MPa.

[0019] Preferably, in the step (5), the sintering temperature is first increased to 550-750°C at a heating rate of 50-80°C / min and kept at this temperature for 1-3 hours, then argon is introduced to increase the pressure to 1-5 MPa, and at the same time, the sintering temperature is increased to 1350-1550°C at a heating rate of 30-50°C / min and sintered for 2-5 hours.

[0020] Preferably, in step (6), a grinder is used for surface grinding, the rotation speed of the grinder is 1500-1800 r / min, and the feed amount of a single reciprocating stroke is 0.03-0.05 mm.

[0021] Another aspect of the present invention provides a ruthenium-tantalum alloy target prepared by the above method. The composition of the ultra-high dense fine-grained ruthenium-tantalum alloy target includes, by atomic percentage, 60 to 90 at.% of ruthenium and the remainder of tantalum.

[0022] Preferably, the ultra-high dense fine-grained ruthenium-tantalum alloy target has a density of ≥99.8% and a target grain size of ≤5 μm.

[0023] Beneficial effects of the present invention:

[0024] The present invention effectively improves the density of the ruthenium-tantalum alloy target material through the comprehensive effect of the preparation method, and at the same time refines the grain size of the ruthenium-tantalum alloy, so that the ruthenium-tantalum alloy target material has more excellent sputtering performance and better adaptability to magnetron sputtering. Therefore, when the ruthenium-tantalum alloy is used as a target material and the integrated circuit film is prepared by magnetron sputtering, the preparation stability is better, the prepared film is more uniform, and the performance of the film is finally improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a fracture morphology diagram of the ruthenium-tantalum alloy target prepared by the present invention. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with specific embodiments.

[0027] In the examples of the present invention, all chemical reagents not specified were commercially available analytically pure for the experiments.

[0028] Example 1

[0029] In this embodiment, the ruthenium-tantalum alloy target is prepared by the following method:

[0030] (1) Mixed powder: An argon atmosphere is filled in a glove box, and ruthenium powder and tantalum powder with a purity greater than 99.99% are used as raw materials. The raw materials are weighed according to 80 at.% of ruthenium powder and 20 at.% of tantalum powder, and loaded into a polytetrafluoroethylene ball mill. The ball mill material is a cemented carbide ball. A plasma ball mill is used for ball milling and mixing. The ball-to-material ratio is 10:1, the ball milling mixing frequency is 10kHz, the time is 10h, and the ball milling is paused for 30 minutes every 30 minutes to obtain a uniformly mixed ruthenium-tantalum mixed powder. Plasma ball milling can effectively keep the powder particle size at a small level, and can even play a role in reducing the powder particle size, realizing powder micro-alloying, which helps to improve the uniformity of the internal composition of the alloy target.

[0031] (2) Low-pressure pre-pressing: The ruthenium-tantalum mixed powder is loaded into a high-strength graphite mold and pre-pressed at low pressure using a hydraulic press. The pressure is 10 MPa and the pressure holding time is 30 minutes. After the pressure holding is completed, the pressure is slowly unloaded.

[0032] (3) Hydrogen reduction of pre-pressed billets: The low-pressure pre-pressed billets are placed in a tubular reduction furnace for hydrogen reduction. The temperature of hydrogen reduction is 500°C, the pressure of the hydrogen atmosphere is 5 MPa, and the reduction time is 3 h to eliminate the oxygen adsorbed on the surface of the pre-pressed billets.

[0033] (4) Spark plasma sintering: The hydrogen-reduced preform is placed in a spark plasma sintering furnace, the mold is wrapped with carbon felt, and the pressure is slowly increased to 30 MPa, and the vacuum degree of the furnace chamber is kept below 10 -2 Pa, the sintering temperature was raised to 1200 °C at a heating rate of 100 °C / min, sintered for 30 min, and then cooled to room temperature with the furnace to achieve uniform control of the microstructure and fine grains, and obtain the SPS sintered blank.

[0034] (5) Low-pressure sintering: Place the SPS sintered blank into a low-pressure sintering furnace and keep the vacuum degree of the furnace chamber at 10 -2 Pa, set the heating rate of 50℃ / min to raise the temperature in the furnace chamber to 550℃ and keep it warm for 3h; then raise the temperature to 1350℃ at a heating rate of 30℃ / min, introduce 2.5MPa of high-purity Ar gas, and sinter for 5h. After sintering, cool it to room temperature with the furnace to obtain an ultra-high-density fine-grained ruthenium-tantalum sintered ingot. Through a lower heating rate and a longer sintering time, the entire sintering process is carried out more slowly, eliminating the microscopic pores inside the alloy and improving the density. At the same time, through two-stage temperature rise sintering, the density of the ruthenium-tantalum sintered ingot is further strengthened.

[0035] (6) Precision machining: The surface of the sintered ingot after low-pressure sintering is ground by a grinder, the grinding speed is 1500r / min, and the feed amount for each reciprocating stroke is 0.03mm, to obtain an ultra-high dense fine-grained ruthenium-tantalum alloy target with a smooth surface and a roughness of ≤1.6μm. The sintered ingot can be processed into a ruthenium-tantalum alloy target product with an appearance size that meets the actual use requirements through precision machining.

[0036] The ruthenium-tantalum alloy target prepared in this embodiment was tested, and the results are shown in Table 1.

[0037] Example 2

[0038] In this embodiment, the ruthenium-tantalum alloy target is prepared by the following method:

[0039] (1) Powder mixing: An argon atmosphere was filled in a glove box. Ruthenium powder and tantalum powder with a purity greater than 99.99% were used as raw materials. The raw materials were weighed according to the ratio of ruthenium powder to 60 at.% and tantalum powder to 40 at.%, and loaded into a polytetrafluoroethylene ball mill. The ball mill material was cemented carbide balls. The ball milling was carried out using a plasma ball mill. The ball-to-material ratio was 20:1. The ball milling mixing frequency was 9 kHz and the time was 8 hours. The ball milling was paused for 30 minutes every 30 minutes to obtain a uniformly mixed ruthenium-tantalum mixed powder.

[0040] (2) Low-pressure pre-pressing: The ruthenium-tantalum mixed powder is loaded into a high-strength graphite mold and pre-pressed at low pressure using a hydraulic press. The pressure is 15 MPa and the pressure holding time is 50 minutes. After the pressure holding is completed, the pressure is slowly unloaded.

[0041] (3) Hydrogen reduction of pre-pressed billets: The low-pressure pre-pressed billets are placed in a tubular reduction furnace for hydrogen reduction. The temperature of hydrogen reduction is 600°C, the pressure of the hydrogen atmosphere is 3 MPa, and the reduction time is 4 h to eliminate the oxygen adsorbed on the surface of the pre-pressed billets.

[0042] (4) Spark plasma sintering: The hydrogen-reduced preform is placed in a spark plasma sintering furnace. The mold is wrapped with carbon felt and slowly pressurized to 40 MPa. The vacuum degree of the furnace chamber is kept below 10 -2 Pa, the sintering temperature was raised to 1300 °C at a heating rate of 120 °C / min, sintered for 15 min, and then cooled to room temperature with the furnace to achieve uniform control of the microstructure and fine grains, and obtain the SPS sintered blank.

[0043] (5) Low-pressure sintering: Place the SPS sintered blank into a low-pressure sintering furnace and keep the vacuum degree of the furnace chamber at 10 -2 Pa, the temperature was raised to 650℃ at a heating rate of 80℃ / min and kept at that temperature for 1.5h; then the temperature was raised to 1500℃ at a heating rate of 50℃ / min, 5MPa of high-purity Ar gas was introduced, and sintering was carried out for 3h. After sintering, the furnace was cooled to room temperature to obtain an ultra-high-density fine-grained ruthenium-tantalum sintered ingot.

[0044] (6) Precision machining: The sintered ingot after low-pressure sintering is surface ground using a grinder with a rotation speed of 1650 r / min and a feed amount of 0.04 mm per reciprocating stroke to obtain an ultra-high dense fine-grained ruthenium-tantalum alloy target with a smooth surface and a roughness of ≤1.6 μm.

[0045] The ruthenium-tantalum alloy target prepared in this embodiment was tested, and the results are shown in Table 1.

[0046] Example 3

[0047] In this embodiment, the ruthenium-tantalum alloy target is prepared by the following method:

[0048] (1) Powder mixing: An argon atmosphere was filled in a glove box. Ruthenium powder and tantalum powder with a purity greater than 99.99% were used as raw materials. The raw materials were weighed according to the ratio of ruthenium powder to 90 at.% and tantalum powder to 10 at.%, and loaded into a polytetrafluoroethylene ball mill. The ball mill material was cemented carbide balls. The ball milling was carried out using a plasma ball mill. The ball-to-material ratio was 30:1. The ball milling mixing frequency was 8 kHz and the time was 9 hours. The ball milling was paused for 30 minutes every 30 minutes to obtain a uniformly mixed ruthenium-tantalum mixed powder.

[0049] (2) Low-pressure pre-pressing: The ruthenium-tantalum mixed powder is loaded into a high-strength graphite mold and pre-pressed at low pressure using a hydraulic press. The pressure is 20 MPa and the pressure holding time is 60 minutes. After the pressure holding is completed, the pressure is slowly unloaded.

[0050] (3) Hydrogen reduction of pre-pressed billets: The low-pressure pre-pressed billets are placed in a tubular reduction furnace for hydrogen reduction. The temperature of hydrogen reduction is 700°C, the pressure of the hydrogen atmosphere is 0.5 MPa, and the reduction time is 5 h to eliminate the oxygen adsorbed on the surface of the pre-pressed billets.

[0051] (4) Spark plasma sintering: The hydrogen-reduced preform is placed in a spark plasma sintering furnace, the mold is wrapped with carbon felt, and the pressure is slowly increased to 50 MPa, and the vacuum degree of the furnace chamber is kept below 10 -2 Pa, the sintering temperature was raised to 1350 °C at a heating rate of 150 °C / min, sintered for 10 min, and then cooled to room temperature with the furnace to achieve uniform control of the microstructure and fine grains, and obtain the SPS sintered blank.

[0052] (5) Low-pressure sintering: Place the SPS sintered blank into a low-pressure sintering furnace and keep the vacuum degree of the furnace chamber at 10 -2 Pa, the temperature was raised to 750℃ at a heating rate of 70℃ / min and kept at that temperature for 1h; then the temperature was raised to 1550℃ at a heating rate of 45℃ / min, 1MPa of high-purity Ar gas was introduced, and sintered for 2h. After sintering, the furnace was cooled to room temperature to obtain an ultra-high-density fine-grained ruthenium-tantalum sintered ingot.

[0053] (6) Precision machining: The sintered ingot after low-pressure sintering is surface ground using a grinder with a grinding speed of 1800 r / min and a feed amount of 0.05 mm per reciprocating stroke to obtain an ultra-high dense fine-grained ruthenium-tantalum alloy target with a smooth surface and a roughness of ≤1.6 μm.

[0054] The ruthenium-tantalum alloy target prepared in this embodiment was tested, and the results are shown in Table 1.

[0055] Table 1

[0056] name Density Average grain size C content O content Example 1 99.85% 3.5μm 40ppm 38ppm Example 2 99.90% 4.2μm 42ppm 37ppm Example 3 99.93% 2.5μm 41ppm 42ppm

[0057] It can be seen from Table 1 that the density of the ruthenium-tantalum alloy prepared by the present invention can be maintained above 99.8%, the average grain size can be maintained below 5 μm, and at the same time, the carbon and oxygen contents in the ruthenium-tantalum alloy target can be maintained at a low level, both not exceeding 50 ppm.

[0058] pass Figure 1 It can be qualitatively seen that the ruthenium-tantalum alloy prepared by the present invention has a higher density and a smaller grain size.

[0059] In the process of preparing ruthenium-tantalum alloy target material of the present invention, low-pressure pre-pressing is first carried out before hydrogen reduction. Under low-pressure conditions, the mixed powder can be compacted to obtain a pre-pressed blank on the basis of reducing the influence on the structural performance of the mixed powder itself. Compared with the state of the mixed powder without dispersion, the pre-pressed blank has a smaller surface area. The main purpose of hydrogen reduction is to remove impurities so that the final ruthenium-tantalum alloy reaches the purity required for normal use. After hydrogen reduction removes impurities, the pre-pressed blank has a smaller surface area, which can reduce the contact area between the pre-pressed blank and the air, thereby reducing the adsorption effect of the pre-pressed blank on oxygen and other impurities in the air, avoiding the introduction of impurities into the pre-pressed blank after impurities are removed, affecting the impurity removal effect, and resulting in a lower purity of the final ruthenium-tantalum alloy.

[0060] During the spark plasma sintering process, high-energy active ions are used to reduce the diffusion resistance of the sintering process and promote particle contact, thereby achieving the purpose of grain refinement. Low-pressure sintering is then used to prevent further plastic deformation of the ruthenium-tantalum alloy billet during the sintering process, thereby maintaining the grain refinement effect of spark plasma sintering. That is, while maintaining the ruthenium-tantalum alloy grains at a smaller size, low-pressure sintering is used to promote the elimination of micropores inside the alloy, significantly improving the density of the ruthenium-tantalum alloy target.

[0061] In summary, the present invention can successfully prepare a ruthenium-tantalum alloy target material with relatively high density and relatively small grain size, so that the ruthenium-tantalum alloy target material has better adaptability to magnetron sputtering, and improves the performance of the ruthenium-tantalum alloy target material in the magnetron sputtering process, which helps to improve the performance of the final thin film product.

[0062] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A method for preparing an ultra-high density fine-grained ruthenium-tantalum alloy target, characterized in that: The preparation method comprises the following steps: (1) Powder mixing: In an argon atmosphere, metal ruthenium powder and tantalum powder are placed in a ball mill, and then ball milled to mix the powders to obtain a mixed powder; (2) low-pressure pre-pressing: the mixed powder obtained in step (1) is placed in a graphite mold and subjected to low-pressure pre-pressing to obtain a pre-pressed blank; (3) Hydrogen reduction: placing the pre-pressed blank obtained in step (2) into a tubular reduction furnace for hydrogen reduction; (4) Spark plasma sintering: placing the preform after hydrogen reduction in step (3) into a spark plasma sintering furnace, and performing spark plasma sintering on the preform to obtain a spark plasma sintered blank; (5) low-pressure sintering: under argon pressure, the spark plasma sintered blank obtained in step (4) is subjected to low-pressure sintering treatment to obtain an ultra-high-density fine-grained ruthenium-tantalum alloy ingot; (6) Precision machining: performing surface grinding on the ultra-high density fine-grained ruthenium-tantalum sintered ingot in step (5) to obtain an ultra-high density fine-grained ruthenium-tantalum alloy target.

2. The method for preparing an ultra-high density fine-grained ruthenium-tantalum alloy target according to claim 1, characterized in that: In the step (1), a plasma ball mill is used for ball milling and powder mixing, the ball-to-material ratio is 10 to 30:1, the ball milling frequency is 8 to 10 kHz, and the ball milling and powder mixing time is 8 to 10 hours.

3. The method for preparing an ultra-high density fine-grained ruthenium-tantalum alloy target according to claim 1, characterized in that: In the step (1), the purity of the metal ruthenium powder and the tantalum powder is ≥99.99%, the particle size of the ruthenium powder is 1 to 5 μm, and the particle size of the tantalum powder is 5 to 20 μm.

4. The method for preparing an ultra-high density fine-grained ruthenium-tantalum alloy target according to claim 1, characterized in that: In the step (2), the pressing pressure is 10 to 20 MPa, and the holding time is 30 to 60 min.

5. The method for preparing an ultra-high density fine-grained ruthenium-tantalum alloy target according to claim 1, characterized in that: In the step (3), the hydrogen reduction temperature is 500-700° C., the hydrogen pressure is 0.5-5 MPa, and the reduction time is 3-5 h.

6. The method for preparing an ultra-high density fine-grained ruthenium-tantalum alloy target according to claim 1, characterized in that: In the step (4), the spark plasma sintering temperature is 1200-1350° C., the sintering time is 10-30 min, and the sintering pressure is 30-50 MPa.

7. The method for preparing an ultra-high density fine-grained ruthenium-tantalum alloy target according to claim 1, characterized in that: In the step (5), the sintering temperature is first increased to 550-750°C at a heating rate of 50-80°C / min and kept at this temperature for 1-3 hours. Then, argon is introduced to increase the pressure to 1-5 MPa. At the same time, the sintering temperature is increased to 1350-1550°C at a heating rate of 30-50°C / min and sintered for 2-5 hours.

8. The method for preparing an ultra-high density fine-grained ruthenium-tantalum alloy target according to claim 1, characterized in that: In the step (6), a grinding machine is used for surface grinding, the rotation speed of the grinding machine is 1500-1800 r / min, and the feed amount of a single reciprocating stroke is 0.03-0.05 mm.

9. The ultra-high density fine-grained ruthenium-tantalum alloy target prepared by the method for preparing an ultra-high density fine-grained ruthenium-tantalum alloy target according to any one of claims 1 to 8, characterized in that: The composition of the ultra-high dense fine-grained ruthenium-tantalum alloy target material includes, by atomic percentage, 60 to 90 at.% of ruthenium, and the remainder is tantalum.

10. The ultra-high density fine-grained ruthenium-tantalum alloy target according to claim 9, characterized in that: The ultra-high dense fine-grained ruthenium-tantalum alloy target material has a density of ≥99.8% and a target material grain size of ≤5 μm.